An Adapted Clinical Measurement Tool for the Key Symptoms of CLN2 Disease. (11th July 2018) - Wyrwich, Kathleen W.; Schulz, Angela; Nickel, Miriam; Slasor, Peter; Ajayi, Temitayo; Jacoby, David R.; Kohlschütter, Alfried
Neuronal ceroid lipofuscinosis type-2 (CLN2) disease is a rare, autosomal recessive, pediatric-onset, neurodegenerative lysosomal storage disease caused by mutations in the TPP1 gene. Cerliponase alfa (Brineura®), a recombinant form of human tripeptidyl peptidase-1, was recently developed as a treatment for CLN2 disease. In clinical trials, the primary end point to evaluate treatment effect was the aggregate score for the motor and language (ML) domains of the CLN2 Clinical Rating Scale, an adaptation of the Hamburg scale's component items that include anchor point definitions to allow consistent ratings in multinational, multisite, clinical efficacy studies. Psychometric analyses demonstrated that the ML score of the CLN2 Clinical Rating Scale and individual item scores are well defined and possess adequate measurement properties (reliability, validity, and responsiveness) to demonstrate a clinical benefit over time. Additionally, analyses comparing the CLN2 Clinical Rating Scale ML ratings to the Hamburg scale's ML ratings demonstrated adequate similarity.